The Cyclical Relation Between Chronic Pain, Executive Functioning, Emotional Regulation, and Self-Management. (29th November 2020) - Caes, Line; Dick, Bruce; Duncan, Christina; Allan, Julia
Abstract: Objective : To propose a new model outlining a hypothesized cyclical relation between executive functioning, emotional regulation, and chronic pain in adolescence and to highlight the likely importance of such a relation for self-management behavior and pain-related disability. Methods : A review of the existing literature that critically explores the role of executive functioning in understanding chronic pain experiences and self-management in adolescence in order to develop the Cyclical model Of Pain, Executive function, emotion regulation, and Self-management (COPES). Results : Growing evidence points towards a potential cyclical relation between chronic pain and impaired executive functioning, which forms the basis of COPES. The COPES model proposes that the relative immaturity of executive functioning in adolescence negatively influences their ability to engage with self-management, which in turn increases adolescents' disability due to pain and contributes to the maintenance of chronic pain, which perpetuates the reduced capacity of executive functioning. The moderating influence of flexible parental support is hypothesized to offset some of these influences. However, the available evidence is limited due to methodological shortcomings such as large variety in executive functioning operationalization, reliance on self-report and cross-sectional designs. Conclusions : It is anticipated that the COPES model will stimulate more systematic, theory-driven research to further our understanding of the links between executive functioning, chronic pain, self-management, and wellbeing. Such enhanced understanding has the potential to drive forward intervention development and refinement aimed at improving self-management uptake and adherence amongst adolescents with chronic pain.